Plasma Fluidized Bed - Du, Changming (Advanced Topics in Science and Technology in China,, 2018)
This book provides a detailed overview of the plasma fluidized bed. It is an innovative tool and generally combines plasma process with another efficient reactor, fluidized bed, providing an excellent method for particulate processes over conventional technology. The development and designs of typical types of plasma fluidized beds, mainly thermal plasma fluidized beds and non-thermal plasma fluidized beds are discussed. The influencing factors on the performance of plasma fluidized beds are analyzed in detail. The mechanism, i.e. the discharge characteristics, hydrodynamics, heat transfer and mass transfer are analyzed to offer a further insight of plasma fluidized beds. Applications of plasma fluidized beds for different areas, including metallurgy extraction, green energy process, environmental protection and advanced materials are presented. The book is a valuable reference for scientists, engineers and graduate students in chemical engineering and relative fields.